1997
DOI: 10.1007/s002280050244
|View full text |Cite
|
Sign up to set email alerts
|

Chronic colchicine treatment does not impair glucose tolerance in familial Mediterranean fever patients

Abstract: Based on these findings, no impairment in glucose dynamics could be demonstrated in chronically colchicine treated patients, compared to untreated controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…10,33 In the current study, participants in the colchicine arm had Previous small, short-term prospective studies in healthy adults had suggested that colchicine might actually worsen metabolic variables by inhibiting insulin secretion by unclear mechanisms. 35,36 However, more recent retrospective studies of individuals with chronic inflammatory conditions found that long-term colchicine use did not have negative effects on insulin secretion or glycaemic control, 37 and might potentially have metabolic benefits. 17 Similarly, our results confirmed that chronic colchicine use does not impair first-phase insulin response or insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…10,33 In the current study, participants in the colchicine arm had Previous small, short-term prospective studies in healthy adults had suggested that colchicine might actually worsen metabolic variables by inhibiting insulin secretion by unclear mechanisms. 35,36 However, more recent retrospective studies of individuals with chronic inflammatory conditions found that long-term colchicine use did not have negative effects on insulin secretion or glycaemic control, 37 and might potentially have metabolic benefits. 17 Similarly, our results confirmed that chronic colchicine use does not impair first-phase insulin response or insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Burstein and colleagues examined the effect of chronic colchicine treatment on glucose-induced insulin secretion on a group of 31 FMF patients treated with colchicine (1-2 mg daily) continuously for between 2 and 13 years (Burstein et al, 1997). They performed an OGTT on all the patients and an IVGTT on each of nine patients randomly chosen from the FMF cohort.…”
Section: H Colchicinementioning
confidence: 99%
“…However, to date, there are scant prospective human clinical data focusing on the metabolic effects of using colchicine to inhibit obesity-induced inflammation. Two retrospective trials have demonstrated no long-term metabolic adverse consequences from colchicine use [97,98]; however, neither of these trials specifically examined its effects in those with obesity-induced inflammation. The LoDoCo (Low-Dose Colchicine) trial prospectively examined the cardioprotective effects of colchicine 0.5 mg daily versus placebo in individuals with stable coronary artery disease, of which 30% had T2DM and over two-thirds were using antihypertensive therapy (and thus had components of the metabolic syndrome).…”
Section: Evaluation Of Hypothesismentioning
confidence: 99%